THE PLACE AND ROLE OF TIME IN HUMAN ACTIVITY - Norkulov, D.T. (PT. Antis International Publisher, 2024)
Background: Time is a crucial but usually underappreciated aspect of human life and societal development. It has an impact on many aspects of society and serves as both a change indicator and a regulator of human behavior. Specific Background: Despite the fact that societies usually divide time into